Influenza-associated morbidity and mortality in South Africa - Cohen, Cheryl (My University, 2015)
Introduction Data on the burden of influenza-associated hospitalisation and mortality in relation to other aetiologies of pneumonia as well as risk groups for severe and complicated disease are important to guide influenza prevention policy. Materials and methods We estimated influenza-related deaths as excess mortality above a model baseline during influenza epidemic periods from monthly age-specific mortality data using Serfling regression models. For individuals aged ≥65 years from South Africa and the United States of America (US) we evaluated influenza-related deaths due to all causes, pneumonia and influenza (P&I) and other influenza-associated diagnoses for 1998-2005. For adults with acquired immune deficiency syndrome (AIDS) aged 25-54 years in South Africa (1998-2005) and the US (pre-highly active antiretroviral therapy (HAART) era: 1987-1994; HAART era: 1997-2005) we estimated deaths due to all-causes and P&I. We prospectively enrolled individuals with severe acute respiratory illness (SARI) at six hospitals in four provinces of South Africa from 2009-2012. Using polymerase chain reaction, respiratory samples were tested for ten respiratory viruses and blood for pneumococcal DNA. Cumulative annual SARI incidence was estimated at one site with available population denominators. Results Age-standardised excess mortality rates amongst seniors were higher in South Africa than in the US (545 vs. 133 per 100,000 for all-causes, p<0.001; 63 vs. 21 for P&I, p=0.03). The mean percent of winter deaths attributable to influenza was 16% in South Africa and 6% in the US, p<0.001. For all respiratory causes, cerebrovascular disease and diabetes age-standardised excess death rates were 4- to 8-fold greater in South Africa than in the US, and the percent increase in winter deaths attributable to influenza was 2- to 4-fold higher. In the US pre-HAART, influenza-related mortality rates in adults with AIDS were 150- (95% confidence interval (CI) 49-460) and 208- (95% CI 74-583) times greater than in the general population for all-cause and P&I respectively and 2.5- (95% CI 0.9-7.2) and 4.1- (95% CI 1.4-13) times higher than in seniors. Following HAART introduction, influenza-related mortality in adults with AIDS dropped 3-6 fold but remained elevated compared to the general population (all cause relative risk (RR) 44, 95% CI 16-12); P&I RR 73, 95% CI 47-113). Influenza-related mortality in South African adults with AIDS was similar to that in the US in the pre-HAART era. From 2009-2012 we enrolled 8723 children age <5 years with SARI. The human immunodeficiency virus (HIV) prevalence among tested children was 12% (705/5964). The overall prevalence of respiratory viruses identified was 78% (6517/8393), which included 26% (n=2216) respiratory syncytial virus (RSV) and 7% (n=613) influenza. The annual incidence of SARI hospitalisation in children age <5 years ranged from 2530-3173 per 100,000 and was 1.1-3-fold greater in HIV-infected than HIV-uninfected children. In multivariable analysis, compared to HIV-uninfected children, HIV-infected children were more likely to be hospitalised >7 days (odds ratio (OR) 3.6, 95% CI 2.8-5.0) and had a 4.2-fold (95% CI 2.6-6.8) higher case-fatality ratio. From 2009-2012, we enrolled 7193 individuals aged ≥5 years with SARI. HIV-prevalence was 74% (4663/6334) and 9% (621/7067) tested influenza positive. The annual incidence of SARI hospitalisation in individuals age ≥5 years ranged from 325-617 per 100,000 population and was 13 to 19-fold greater in HIV-infected individuals (p<0.001). On multivariable analysis, compared to HIV-uninfected individuals, HIV-infected individuals were more likely to be receiving tuberculosis treatment (OR 2.1, 95% CI 1.3-3.2), have pneumococcal infection (OR 2.2, 95% CI 1.6-2.9), be hospitalised for longer (>7 days rather than <2 days OR 2.4, 95% CI 1.8-3.2) and had a higher case-fatality ratio (8% vs. 5%; OR 1.6, 95% CI 1.2-2.2), but were less likely to be infected with influenza (OR 0.6, 95% CI 0.5-0.8). Influenza was identified in 9% (1056/11925) of patients of all ages enrolled in SARI surveillance from 2009-2011. Among influenza case-patients, 44% (358/819) were HIV-infected. Age-adjusted influenza-associated SARI incidence was 4-8 times greater in HIV-infected (186-228 per 100,000 population) than HIV-uninfected (26-54 per 100,000 population). On multivariable analysis, compared to HIV-uninfected individuals, HIV-infected individuals with influenza-associated SARI were more likely to have pneumococcal co-infection (OR 2.3, 95% CI 1.0-5.0), influenza type B than type A (OR 1.6, 95% CI 1.0-2.4), be hospitalised for 2-7 days (OR 2.8 95% CI 1.5-5.5) or >7 days (OR 4.5, 95% CI 2.1-9.5) and more likely to die (OR 3.9, 95% CI 1.1-14.1). Discussion and conclusions The mortality impact of seasonal influenza in the South African elderly may be substantially higher in an African setting compared to the US. Adults with AIDS in South Africa and the US experience substantially elevated influenza-associated mortality rates, which although lessened by widespread HAART treatment does not completely abrogate the heightened risk for influenza illness. HIV-infected children and adults also experience substantially elevated incidence of hospitalisation for influenza-associated SARI and have higher case-fatality ratios. Influenza is commonly detected amongst children (7%) and adults (9%) with SARI. Less frequent identification of influenza amongst HIV-infected than -uninfected individuals aged ≥5 years likely reflects increased relative burden and role of other opportunistic pathogens such as pnuemococcus and Pneumocystis jirovecii. Improved access to HAART for HIV-infected individuals and vaccination against influenza virus amongst HIV-infected individuals, young children and the elderly, where the influenza burden is great may reduce the high burden of hospitalisations and mortality associated with influenza.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, October 2014
Keywords: Influenza--epidemiology--South Africa; Influenza--mortality--South Africa